Những câu hỏi liên quan
ST
Xem chi tiết
II
Xem chi tiết
LC
12 tháng 6 2016 lúc 12:17

Ta có: 8.(x-2013)2+y2=25

=>y2=25-8.(x-2013)2

Vì \(\left(x-2013\right)^2\ge0=>8.\left(x-2013\right)^2\ge0=>25-8.\left(x-2013\right)^2\le25-0\)

=>\(y^2\le25=>y\le5\)

=>\(y\in\left\{1,2,3,4,5\right\}=>y^2\in\left\{1,4,9,16,25\right\}\)

Vì 25:8 dư 1, 8.(x-2013)2 chia 8 dư 0

=>25-8.(x-2013)2 chia 8 dư 1

=>y2 chia 8 dư 1

mà \(y^2\in\left\{1,4,9,16,25\right\}\)

=>y2=25=>y=5

25-8.(x-2013)2=25

=>8.(x-2013)2=0

=>(x-2013)2=0

=>x-2013=0

=>x=2013

Vậy x=2013, y=5

Bình luận (0)
DP
Xem chi tiết
L2
Xem chi tiết
TP
18 tháng 10 2018 lúc 9:33

22 . x + 2y = 2013

=> 4 . x + 4 = 2013

=> 4x = 2009

=> x = 502,25

Bình luận (0)
TP
18 tháng 10 2018 lúc 9:35

y = 2 nữa nhé mik bị thiếu

Bình luận (0)
HS
18 tháng 10 2018 lúc 9:37

\(2^2\cdot x+2^y=2013\)   => Thay thế y= 2

\(\Rightarrow4\cdot x+2^2=2013\)

\(\Rightarrow4\cdot x+4=2013\)

\(\Rightarrow4\cdot x=2013-4\)

\(\Rightarrow4\cdot x=2009\)

\(\Rightarrow x=\frac{2009}{4}=502,25\)

Vậy x = 502,25

Bình luận (0)
NA
Xem chi tiết
DQ
Xem chi tiết
TT
Xem chi tiết
LL
23 tháng 1 2016 lúc 13:56

a) 2x2 + x - 18 chia hết cho x - 3

\(\Rightarrow\) (2x . x) + x - 18 chia hết cho x - 3

\(\Rightarrow\) 3x + x - 18 chia hết cho x - 3

\(\Rightarrow\) 4x - 18 chia hết cho x - 3

\(\Rightarrow\) 4x - 12 - 6 chia hết cho x - 3

\(\Rightarrow\) 4(x - 3) - 6 chia hết cho x - 3

\(\Rightarrow\) (-6) chia hết cho x - 3

\(\Rightarrow\) x - 3 \(\in\) Ư(-6) = {-1; -2; -3; -6}

\(\Rightarrow\) x \(\in\) {2; 1; 0; -3}



b) 25 - y2 = 8(x - 2013)2

25 - y . y = 8(x - 2013)(x - 2013)

25 - 2y = 8 - 2(x - 2013)

25 - 2y = 8 - (2x - 2 . 2013)

25 - 2y = 8 - (2x - 4026)

25 - 2y = 8 - 2x + 4026

25 - 2y = (8 + 4026) - 2x

25 - 2y = 4034 - 2x


 

Bình luận (0)
LL
23 tháng 1 2016 lúc 18:06

a) 2x2 + x - 18 chia hết cho x - 3

\(\Rightarrow\) (2x . x) + x - 18 chia hết cho x - 3

\(\Rightarrow\) 3x + x - 18 chia hết cho x - 3

\(\Rightarrow\) 4x - 18 chia hết cho x - 3

\(\Rightarrow\) 4x - 12 - 6 chia hết cho x - 3

\(\Rightarrow\) 4(x - 3) - 6 chia hết cho x - 3

\(\Rightarrow\) (-6) chia hết cho x - 3

\(\Rightarrow\) x - 3 \(\in\) Ư(-6) = {-1; -2; -3; -6}
\(\Rightarrow\) x \(\in\) {2; 1; 0; -3}



b) 25 - y2 = 8(x - 2013)2


25 - y . y = 8(x - 2013)(x - 2013)

25 - 2y = 8 - 2(x - 2013)

25 - 2y = 8 - (2x - 2 . 2013)

25 - 2y = 8 - (2x - 4026)

25 - 2y = 8 - 2x + 4026

25 - 2y = (8 + 4026) - 2x

25 - 2y = 4034 - 2x

Bình luận (0)
LL
23 tháng 1 2016 lúc 18:07

@: Sửa

a) 2x2 + x - 18 chia hết cho x - 3

\(\Rightarrow\) (2x . x) + x - 18 chia hết cho x - 3

\(\Rightarrow\) 3x + x - 18 chia hết cho x - 3

\(\Rightarrow\) 4x - 18 chia hết cho x - 3

\(\Rightarrow\) 4x - 12 - 6 chia hết cho x - 3

\(\Rightarrow\) 4(x - 3) - 6 chia hết cho x - 3

\(\Rightarrow\) (-6) chia hết cho x - 3

\(\Rightarrow\) x - 3 \(\in\) Ư(-6) = {-1; -2; -3; -6}


\(\Rightarrow\) x \(\in\) {2; 1; 0; -3}



b) 25 - y2 = 8(x - 2013)2


25 - y . y = 8(x - 2013)(x - 2013)

25 - 2y = 8 - 2(x - 2013)

25 - 2y = 8 - (2x - 2 . 2013)

25 - 2y = 8 - (2x - 4026)

25 - 2y = 8 - 2x + 4026

25 - 2y = (8 + 4026) - 2x

25 - 2y = 4034 - 2x

Bình luận (1)
ST
Xem chi tiết
NH
Xem chi tiết